Determinasi Rotasi KAP, Tenur Auditor Dan Kualitas Audit Terhadap Manajemen Laba - Amasti, Novia; Surbakti, Lidya Primta; Warman, Edi (Institut Bisnis dan Informatika Kesatuan, 2020)
The purpose of this study was to determine the effect of KAP rotation, auditor tenure and audit quality on earnings management. This study also uses leverage, profitability and firm size as control variables. In this study to measure earnings management variables using the Modified Jones Model. the population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2018. The number of samples processed was 366 samples. The analytical method used is panel data linear regression analysis with Stata version 13. The results of this test show that KAP rotation and audit quality has no effect on earnings management while auditor tenure has effect on earnings management. Keywords : KAP rotation, auditor tenure, audit quality, and earnings management.